The Hostile City of Love and Antibodies of Hate - Demirsu, Ipek (Global Populisms, 2024)
Demirsu offers an engaging comparative analysis of antagonistic social actors co-existing in Verona, a mid-sized city in northeast Italy renowned as the fortress of the far-right. This rich multidimensional analysis explores the intersection of space, identity, and social movements, by delving into the evolution of competing actors and their contending positions on identity and belonging as manifested through urban spaces. While the city and its touristic heritage are promoted for a transnational identitarian network, the protracted struggles of grassroots actors demonstrate democratic potentials for the bottom-up realization of inclusive and pluralist possibilities in hostile settings. The book traces the ways in which collective identity and collective action of social actors are shaped by their relationship to the space in which they operate, with ramifications for places beyond.